Masculinities, humour and care for penile cancer: a qualitative study. (25th February 2014) - Branney, Peter; Witty, Karl; Braybrook, Debbie; Bullen, Kate; White, Alan; Eardley, Ian
Abstract Aim To explore how men with penile cancer construct humour in relation to their diagnosis and treatment. Background Functionalist, relief and incongruity theories attempt to account for humour, but there is a dearth of empirical evidence in nursing care. This is particularly so in relation to a condition like penile cancer where some nurses think that humour in their interactions with patients would be inappropriate. Design The study employed a participative, mixed‐qualitative‐methods design. Method Focus groups and patient‐conducted interviews were both used during a one‐day 'pilot workshop' in March 2011. The data were initially analysed using framework analysis. This paper explores the theme of humour in depth. Findings Humour helped participants make light of their condition, which meant that they could laugh about the consequences of treatment ('laughing about urination') and build rapport with health professionals ('humour with health professionals'). Nevertheless, the use of humour was less important than the treatment of their cancer ('humour discounted') and there was a fear that they would be subject to ridicule because of their condition ('fear of ridicule'). Conclusion The findings suggest a combination of functionalist, relief and incongruity theories of humour; the emotions these men experience are contained (functionalist) and released (relief) through humorous interaction, and the potential for comedy lies in an incongruity between what is expected socially and the experiences of these men, for example, around expectations that men use urinals in public toilets. Nurses should continue to use humour to build rapport with patients, should they judge this to be appropriate, although they may want to avoid jokes about sexual and urinary functioning until after treatment.